Ethnic differences in mortality from sudden infant death syndrome in New Zealand. Issue 6869 (2nd January 1993) - Mitchell, E A; Stewart, A W; Scragg, R; Ford, R P; Taylor, B J; Becroft, D M; Thompson, J M; Hassall, I B; Barry, D M; Allen, E M
Abstract : OBJECTIVES–To examine the factors which might explain the higher mortality from sudden infant death syndrome in Maori infants (7.4/1000 live births in 1986 compared with 3.6 in non-Maori children). DESIGN–A large nationwide case control study. SETTING–New Zealand. 485 infants who died of sudden infant death syndrome were compared with 1800 control infants. There were 229 Maori and 240 non-Maori cases of sudden infant death syndrome (16 cases unassigned) and 353 Maori and 1410 non-Maori controls (37 unassigned). RESULTS–Maori infants had 3.81 times the risk (95% confidence interval 3.06 to 4.76) of sudden infant death syndrome compared with non-Maori infants. The risk factors for sudden infant death syndrome within groups were remarkably similar. When Maori and non-Maori controls were compared the prevalence of many of the known risk factors was higher in Maori infants. In particular, mothers were socioeconomically disadvantaged, younger, and more likely to smoke and their infants were of lower birth weight and more likely to share a bed with another person. Multivariate analysis controlling for potential confounders found that simply being Maori increased the risk of sudden infant death syndrome by only 1.37 (95% CI = 0.95 to 2.01), not statistically significantly different from 1. Population attributable risk was calculated for prone sleeping position, maternal smoking, not breast feeding, and infants sharing a bed with another person. In total these four risk factors accounted for 89% of deaths from sudden infant death syndrome in Maori infants and 79% in non-Maori infants. CONCLUSION–The high rate of sudden infant death syndrome among Maori infants is based largely on the high prevalence in the Maori population of the major risk factors. Other risk factors, not related to ethnicity, probably explain remaining differences between Maori and non-Maori children.